In vitro cytotoxicity and apoptosis inducing effect of an antimicrobial peptide th1-5 against human breast adenocarcinoma cell line mcf7 - Khamsah Suryati, Mohd; Md.Sarwar, Jahan; Mohammed Al-Kassim, Hassan; Wan Atirah, Azemin (2015)
Breast cancer is the leading cause of cancer death among women globally and is the most common form of cancer affecting women in Malaysia. Most anticancer drugs present serious drawbacks including resistance and severe host toxicity owing to their poor selectivity towards cancer cells; hence the need to search for alternative chemotherapeutic agents. Tilapia hepcidin is an antimicrobial peptide of fish origin. A synthesized isoform of the peptide designated as TH1-5 was investigated for cytotoxicity against human breast adenocarcinoma MCF7 and normal mouse embryonic fibroblast NIH/3T3 cell lines using the MTT assay. Mode of cell death was also evaluated using acridine orange/ propidium iodide double staining, along with annexin V apoptosis assay. Results showed TH1-5 to be cytotoxic to MCF7 with a half-maximal inhibitory concentration (IC50) of 20µg/ml but less cytotoxic to NIH/3T3. Fluorescence microscopy investigation for mode of cell death revealed majority of the cells underwent apoptotic cell death after 24, 48 and 72 hours of treatment. This study has shown that TH1-5 exert cytotoxic activity and induce apoptosis towards breast cancer cell line, and could be a potential alternative for cancer chemotherapy. Further study is ongoing to evaluate DNA damage by comet assay and to determine the phase of cell cycle arrest.